MELHORIA DE QUALIDADE: UM ESTUDO SOBRE OS IMPACTOS DOS REVESTIMENTOS NA CORROSÃO DO ALUMÍNIO - Guazelli, Caio; Neto, Antonio Faria (Revista Ciências Exatas, 2017)
Aluminum and its alloys are frequently used on the global stage and are widely applied in the fabrication of refrigeration and air conditioning industries. They are currently used in the manufacture of heat exchangers, predominantly two types of aluminum alloys: A8079 and A8006. Based on this, this research studies a real case of aluminum corrosion applied to heat exchangers installed in coastal regions. In each case, accelerated corrosion was observed in the heat exchangers, thus compromising their operation and useful life of the equipment installed under the above mentioned conditions. Therefore, the main objective of this project was to study the effect of inhibiting corrosion layers and the impacts of the production process on the corrosion of aluminum heat exchangers. This research aimed to understand the problem of corrosion of aluminum used in heat exchangers and the factors that affect the strength characteristics of aluminum corrosion when applied in aggressive conditions, considering its technical and technological principles and dimensions. The focus of this research was to apply protective techniques in order to increase the corrosion resistance of aluminum fins, and this study was conducted in the manufacturing process of an American Multinational Corporation. The methodology consisted of a combination of both explanatory and experimental research, and based on the findings of the research the variables that possibly influence the problems in the objective in this study. Heat exchangers are made of aluminum alloy A8006, produced by eccentric presses designed specifically for the manufacture of fins. As options were created to solve a problem means were presented in order to assist with development and future implementation in industry, the project achieved its purpose. The results demonstrate that when coatings were applied on a heat exchanger a higher corrosion resistance was present than their counterparts that didn’t use protection.